A Rapid Effervescent Route to Rational Activation of Cu/g‐C3N4 and bulk MoS2 Cocatalyst for Highly Efficient and Robust Photo‐Fenton Process (Adv. Mater. Interfaces 35/2022). Issue 35 (12th December 2022) - Li, Wenxin; Ding, Chenjie; Kang, Shifei; Gao, Weikang; Yang, Yang; Cui, Lifeng
Abstract : Photo‐Fenton Systems The activation of commercial bulk MoS2 rather than expensive MoS2 nanosheets for boosted Fenton reaction is challenging. In article number 2201552, Wenxin Li and colleagues demonstrate that the acidic microenvironment provided by the effervescent treated Cu/g‐C3 N4 allows the direct activation of bulk MoS2, forming an ideal photo‐Fenton system towards sustainability.